GENERAL CHARACTERISTICS OF MIGRATION PROCESSES’ REGULATION IN THE REGION (ON THE BASIS OF OMSK REGION) - V. S. Polovinko (Вестник СибАДИ, 2018)
Introduction. The article discusses the questions of regulation of migration processes. The research material is presented basing on the study of population migration expectations of Omsk region,which is carried out by the author of the article.Materials and methods. The empirical analysis provides the definition of the methodological prerequisites for the model regulation development. The author identifies three approaches that become the basis for the following model: systemic, institutional and program budgeting. According to the theoretical analysis the necessity and possibility of the regional migration policy development are proved. The justification for the term “regulation” usage instead of the concept “control”, because of the institutional approach and migration expectations, which are based on informal institutions, is presented. Additionally, the thesis about the correlation of objective and subjective in the formation of migration expectations is developed in the research.Results. Distinguishing the concept of “cause” and “factors”, the author clarifies the classification of migration factors and highlights the political, social, economic and geographical environment. The article shows that the political environment is more related to parameters of external region’s position. The research reveals the important factor of migration in conditions of excessive differentiation of regions development, which is distant from the central regions of the Russian Federation and the cultural and recreational values, tourism opportunities, recreation in such cities are more available than in Omsk region. As the result, the research shows the economic environment depends from the external conditions (the economic policy of the country, the stage of development of Russian economy, the tax policy, etc.) and internal conditions (policy on enterprises, supporting industries, subsidies, grant support, investment attractiveness of the region, etc.).Therefore, economic environment of the region significantly influences on the Federal policy, especially on the regulation of migration processes based on the characteristics of the external and internal environment.Conclusion. The author concludes that there are needs to provide additional indicators of the effectiveness of migration management in the region, which would significantly help to monitor the attractiveness of the region as a whole and as separate directions.